2018
DOI: 10.1002/dev.21769
|View full text |Cite
|
Sign up to set email alerts
|

Flawed mothering or infant signaling? The effects of deficient acoustic cues on ovine maternal response

Abstract: The neonate distress cry, which displays a similar acoustic structure across a range of mammalian species, is highly effective in attracting, even compelling, parental care. However, if this cry is defective, as found in human and rodent neonates with poor neurobehavioral function, is the signal less enticing? Using playback recordings of a ewe's own co-twins as stimuli in a two choice test, we compared the preference of each sheep dam for acoustic features of lamb distress calls to assess the impact of signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…This could notify a computer to turn on fans and open windows to increase the airflow. Lamb vocalizations have also been analysed and shown that calls that reflect poor vocal fold engagement and arousal were less likely to be preferred by their parents [150]. This suggests that automated analysis of vocalizations could be an indicator of offspring quality.…”
Section: Summary and Recommendationsmentioning
confidence: 99%
“…This could notify a computer to turn on fans and open windows to increase the airflow. Lamb vocalizations have also been analysed and shown that calls that reflect poor vocal fold engagement and arousal were less likely to be preferred by their parents [150]. This suggests that automated analysis of vocalizations could be an indicator of offspring quality.…”
Section: Summary and Recommendationsmentioning
confidence: 99%
“…Within days after birth, most lambs can find their mother when hidden behind a canvas (Shillito and Alexander 1975;Nowak 1991). The acoustic features of a lambs' bleat are an important part of the social bond between ewes and their lambs, when this cue is deficient, there is a negative impact on the maternal response (Morton et al 2018). Ewes are able to discriminate between the bleats of their own lambs and those of an alien lamb 24 h following birth (Sèbe et al 2007), and lambs able to discern the acoustic signature of their mother at 48 h old (Sèbe et al 2007).…”
Section: Reproduction Lambing/calving and Motheringmentioning
confidence: 99%
“…For example, some adult Australian sea lions exhibit aggressive reactions to food solicitation by unrelated young (Gwilliam et al, 2008). In mammals, parent–offspring recognition is mostly unidirectional (i.e., parents recognize their own offspring), but a few mammals, e.g., narwhal, Monodon Monoceros (Ames et al, 2021); harbor seal, Phoca vitulina (Ravignani et al, 2019); and sheep, Ovis aries (Morton et al, 2018), have bidirectional recognition between parents and their infants.…”
Section: Introductionmentioning
confidence: 99%